(3eMGSHI GdCOhGJ GdeGdjI hab GdfXGe GdeMGSHj GdeGdj heYGjjQ GdeMGSHI GdOhdjI (BLAS/IFRSs - (3HhSHYjf(B, (3JSYOjJs ((3GdLRGFQ(B:s (3GdfTQ GdLGeYj GdLOjO(B,s, 2018)
(3jJfGhd gPG GdcJGH eaGgje YGeI Mhd GdfXGe GdeMGSHj GdeGdj YeheG heYGjjQ GdeMGSHI GdOhdjI, hGdJSLjd GdeMGSHj dddCOhGJ GdeGdjI hab GdfXGe GdeMGSHj GdeGdj hGdeYGjjQ GdOhdjI Ydi hLg GdNUhU , hgh ehLg aj GdZGdH dLejY GdWdHI JNUU eM(B)(3GSHI heGdjI aj LejY GdCWhGQ hEdi cd egfj GdeMGSHI (B.s
(3GdeQGLY U(B.199s
Keywords: (3GdfXGe GdeMGSHj GdeGdj (B- (3GdLRGFQs; (3GdeMGSHI GdJMdjdjIs; (3eYGjjQ GdeMGSHIs